Bioinformatics analysis of the ribosomal protein, Rpl27, Rpl37a and Rpl41:3-D protein modeling and protein-protein interaction prediction - Chan, Stella Li Li (Universiti Malaysia Sarawak (UNIMAS), 2012)
Ribosomal proteins (RP) are constituents of ribosome that is important in protein biosynthesis and likely to have extraribosomal functions. Many RPs are related to various diseases and cancers. From previous studies, RPL27, RPL37a and RPL41 gene were reportedly downregulated in all cell lines derived from Nasopharyngeal Carcinoma (NPC) tissues compared to the normal counterpart. Thus, present study aimed to understand the three genes in protein level and its interaction with other proteins. The methods used RPL27, RPL37a and RPL41 3-D (3-Dimension) protein models to search for structural neighbor in predicting protein-protein interaction. Subsequently, the structural neighbors and their partners were docked to predict functions. As a result, RPL27 revealed interaction with SYNJ2 and UBC9 in dock complex. RPL27 was predicted to mediate RNA binding protein and deregulate sumoylation. Additionally, RPL37a interacted with CTNNBI, SCMH I and ATBFI. RPL37a was predicted to deregulate Wnt degradation pathway and inhibit~ C8tenin migration. RPL37a might also regulate homeotic transcription. Further studies such as alanine scanning mutagenesis can provide deeper insight on protein recognition mechanism and identification of hot spots for protein kinetic studies.